Kematangan emosi remaja dalam pengentasan masalah - Nia Febbiyani Fitri; Bunga Adelya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
Adolescence is often called a period of unstable. At that time a teenager was often involved in various problems. And he will have difficulty in overcoming the problem. At that time a teenager will be difficult to determine between right and wrong, they tend to be easily influenced by friends and the environment. In such circumstances the need for the formation of emotional maturity, as well as the support and guidance of parents, teachers BK, and the environment he was. This writing aims to reveal a picture of students' emotional maturity in alleviating the problem. Keywords: Emotional maturity, Teacher BK, and parents